Balancing the Tensions between Rationalization and Creativity in the Video Games Industry - TSCHANG, Feichin, Ted (Institutional Knowledge at Singapore Management University, 2007)
This paper investigates the forces that influence creativity in the video games industry. We adopt a qualitative approach to guide the development of grounded theory across multiple levels of analysis, including the industry (consisting of multiple actors), organizational, and individual creator levels. Our study shows that business and production interests currently drive the rationalization of video game production. There is a maturing trend, with product designs becoming well established as genres, and consumers and publishers desiring incrementally innovative games. This leads publishers to focus on acquiring intellectual property, and publishers and studios alike to make incrementally innovative sequels. The increasing complexity of products leads to further rationalization in their development. However, the need to satisfy consumers' continually evolving tastes and game developers' inclinations to be creative also creates tensions with these rational forces. Different actors balance these tensions differently. Studios may seek to balance these by shifting between more and less innovative products, by creating original intellectual property to increase their bargaining power with publishers, and by iterating and repositioning products during development to adapt them to the market. Publishers may enhance their portfolio by hiring highly creative designers into their stable. New products are created through combinative creativity, that is, the recombination of existing ideas from different sources into new products. The connection of combinative mechanisms with the balancing behavior at the firm level provides a means for understanding the evolution of innovative products and, therefore, industries. [PUBLICATION ABSTRACT]